2005
DOI: 10.1557/jmr.2005.0210
|View full text |Cite
|
Sign up to set email alerts
|

In situ Synthesis of Nickel Ferrite Nanoparticle/organic Hybrid

Abstract: A NiFe 2 O 4 particle/organic hybrid was synthesized in situ from iron-organic and nickel organic compounds below 100°C. A mixture of nickel (II) acetylacetonate (NA) and iron (III) 3-allylacetylacetonate (IAA) was hydrolyzed and polymerized yielding spinel oxide particle/oligomer hybrid. X-ray diffraction analysis revealed that the crystallinity of spinel particles was dependent upon the hydrolysis conditions of NA-IAA. Nanocrystalline nickel ferrite particles around 10 nm were uniformly dispersed in the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…To this end, syntheses of monodisperse Fe 3 O 4 nanoparticles by the thermal decomposition of metal-organics at high temperatures ranging from 200 to 300 1C have been recently reported [11][12][13]. The authors reported the syntheses of spinel ferrite particle/organic hybrids below 100 1C by using precursors with chelated Fe-O and M-O bonds, which were hydrolyzed with methylhydrazine (MH) [14][15][16]. However, the spinel particles in the hybrids had sizes of less than 10 nm, and the particles were superparamagnetic.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, syntheses of monodisperse Fe 3 O 4 nanoparticles by the thermal decomposition of metal-organics at high temperatures ranging from 200 to 300 1C have been recently reported [11][12][13]. The authors reported the syntheses of spinel ferrite particle/organic hybrids below 100 1C by using precursors with chelated Fe-O and M-O bonds, which were hydrolyzed with methylhydrazine (MH) [14][15][16]. However, the spinel particles in the hybrids had sizes of less than 10 nm, and the particles were superparamagnetic.…”
Section: Introductionmentioning
confidence: 99%